UMS Administrative staff’s feedback and experience in the ‘English for Workplace Communication’ course - Kamsilawati Kamlun; Chelster Sherralyn Jeoffrey Pudin; Eugenia Ida Edward; Irma Wani Othman (Global Academic Excellence, 2022)
The feedback from course participants on what should be included in a programme or course is crucial for further improvement. In light of this setting, this study explores how well the course objectives are met by the "English for Workplace Communication" course. Such input is primarily intended to improve the course's quality and to give the facilitators immediate feedback. The study focuses on how well the administrative staff understands the course material, critical to their demands for oral and written communication in the workplace. A survey was conducted with a qualitative method using a reflective journal on a group of administrative personnel at Universiti Malaysia Sabah. The larger of these dealt with aspects of oral and written communication and the course’s overall reflection. The study's findings discussed the participants' input on the ‘English for Workplace Communication' and their experiences during the one-day course. These positively integrated learning conditions may lead to productive performance, not only in the professional competence of participants but may also affect their English proficiency.